Arab Republic of Egypt : Fourth Review Under the Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Argentina's Fourth Review under the Extended Arrangement under the Extended Fund Facility (EFF). The paper highlights that Egypt's macroeconomic situation has improved markedly since the initiation of the authorities' reform program in November 2016. The liberalization of the foreign exchange market, prudent monetary policy, and ambitious fiscal consolidation has helped stabilize the macroeconomic environment. Growth has accelerated; external and fiscal deficits have narrowed; international reserves have risen; and public debt, inflation, and unemployment have declined. The external environment has shifted in recent months, posing new policy challenges. The tightening of global financial conditions and heightened global risk aversion have contributed to a pullback by investors from emerging markets. The outlook remains favorable, provided policies agreed under the program are implemented, but the balance of risks has shifted. The authorities' prudent policies have been instrumental in preserving macroeconomic stability, even as the external environment has weakened notably. The IMF staff supports the authorities' request for the completion of the fourth review under the Extended Arrangement under the Extended Fund Facility.